A short form of the Maximization Scale - Gergana Y. Nenkov; Maureen Morrin; Andrew Ward; Barry Schwartz; John Hulland (Judgment and Decision Making, 2008)
We conducted an analysis of the 13-item Maximization Scale (Schwartz et al., 2002) with the goal of establishing its factor structure, reliability and validity. We also investigated the psychometric properties of several proposed refined versions of the scale. Four sets of analyses are reported. The first analysis confirms the 3-part factor structure of the scale and assesses its reliability. The second analysis identifies those items that do not perform well on the basis of internal, external, and judgmental criteria, and develops three shorter versions of the scale. In the third analysis, the three refined versions of the scale are cross-validated to confirm dimensionality, reliability, and validity. The fourth analysis uses an experiment in an investment decision making context to assess the reliability and nomological validity of the refined scales. These analyses lead us to conclude that a shorter, 6-item Maximization Scale performs best and should be used by future researchers. It is hoped that clarification of the conceptual underpinnings of the maximization construct and development of a refined scale will enhance its use among researchers across several of the social science disciplines.